2016
DOI: 10.3390/ijerph13080832
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Health Risk Assessment of Metals in Soils in the Vicinity of Industrial Sites in Dongguan, China

Abstract: Exponential industrialization and rapid urbanization have resulted in contamination of soil by metals from anthropogenic sources in Dongguan, China. The aims of this research were to determine the concentration and distribution of various metals (arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb) and zinc (Zn)) in soils and identify their potential health risks for local residents. A total of 106 soil samples were collected from the vicinity of industrial sites in Dong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…It can be clearly seen that both vegetable samples considered in this study are highly loaded with Hg residues and possibly imposing significant health risk to the population consuming the vegetables. The levels of Hg obtained in this study was observed to dangerously exceed the maximum limit value in vegetables as reported by Li et al, [53] and Liu et al [73].…”
Section: Levels Of Heavy Metals In Soil Samples the Levels Of Heavy supporting
confidence: 71%
See 1 more Smart Citation
“…It can be clearly seen that both vegetable samples considered in this study are highly loaded with Hg residues and possibly imposing significant health risk to the population consuming the vegetables. The levels of Hg obtained in this study was observed to dangerously exceed the maximum limit value in vegetables as reported by Li et al, [53] and Liu et al [73].…”
Section: Levels Of Heavy Metals In Soil Samples the Levels Of Heavy supporting
confidence: 71%
“…The levels of Cr, Hg, Ni and Co in the soil sample under tomato cultivation were found to be 36. 23 [44] c [11] d [54] https://doi.org/10.1371/journal.pone.0227883.t003 [53] c European union standards [54] d Dutch target value [73] https://doi.org/10.1371/journal.pone.0227883.t004…”
Section: Levels Of Heavy Metals In Soil Samples the Levels Of Heavy mentioning
confidence: 99%
“…The heavy metals do not undergo microbial or chemical degradation, persisting for a long time after their introduction into the soil (Adriano, 2001). The pollution of the soils by the heavy metals poses a serious threat to ecosystems and human health (Liu et al, 2016). Studies have shown that the pollution by heavy metals affects plant growth and genetic variation, changes the composition of the soil microbial community, and reduces microbial activity (Ellis, Morgan, Weightman, & Fry, 2003;Hong, Si, Xing, & Li, 2015;Li et al, 2006;Linton, Shotbolt, & Thomas, 2007;Moffett et al, 2003;Müller, Westergaard, Christensen, & Sørensen, 2001;Singh et al, 2014;Xie et al, 2016;Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Soil is very important fundamental of natural resource for human survival [1]. Plot of land is important for recycling and redistribution of nutritious elements.…”
Section: Introductionmentioning
confidence: 99%